(untitled) (Globalization and Business, 2023)
Many countries suffer from Balance of Payments deficits. However, proper analysis is needed to determine how systemic, strategically balanced, and objective it is. The pandemic has proven to be an excellent diagnostician for assessing the robustness of current economic strategies in general and in relation to the Balance of Payments. It, like the litmus paper, highlighted the strengths and weaknesses of the economic strategies implemented by the countries. And that should be the main lesson the world has learned from the pandemic. Georgia, with persistent Balance of Payments deficit, is becoming increasingly vulnerable to global changes caused by pandemic processes. The current account deficit in 2020 was 12.5 percent of GDP, up from 5.5 percent in 2019. The development of a worse-case scenario for the growth of the deficit was significantly hampered by the increase in remittances inflows, which was less expected in the context of global lockdowns around the world. However, in reviewing developments over the last two decades, the paper finds that the still-high dependence of current account on remittances continues to maintain the volatility of Balance of Payments. Moreover, favorable conditions for the development of international tourism in the country have raised high expectations for this activity, although this sector is very sensitive to a number of external and global factors, as confirmed by the current pandemic. Thus, the article recommends considering international tourism as an additional source of foreign exchange inflows into the country, and not as one of the main and decisive ones. The deterioration of the Balance of Payments and the reduction of foreign exchange earnings create unfavorable prospects in terms of dealing with growing international financial liabilities. According to 2020 statistical data, the country's international financial liabilities were 2.3 times higher than GDP, of which debt liabilities - 129.9 percent of GDP, while the total foreign exchange inflows of the Balance of Payments, which are intended to serve these liabilities, in the same year amounted to only 55.4 percent of GDP. These data show that there are no alternatives to choosing the right strategy for achieving a reasonable relationship between trajectories of external liabilities and foreign exchange earnings, taking measures to improve the Balance of Payments. The purpose of this article is to clarify the nature of the country's Balance of Payments deficit; How realistic the prospect of mitigating the degree of vulnerability to global factors is in a small economy with limited resources; How we can turn a problem into an opportunity. On the other hand, it is unknown when the crisis, known as COVID-19, will stop finally, it is important to critically evaluate both the pros and cons of a given economic policy "... in order to make the economic development agenda more rational, responsive, results- and long-term perspectives oriented” (Aslamazishvili 2020).